Vertical tillage effects on yield, disease and pathogens, and soil properties - Whitehair, Anthony (Kansas State University, 2014)
In the Midwest there has been an increase in the number of vertical tillage (VT) implements sold and a large push in marketing these newer implements to producers. Vertical tillage is defined as shallow tillage, usually in the top 5 to 7.5 cm of the soil and results in no horizontal disturbance of the soil. The objective was to determine the short-term (one growing season) effects of a vertical-tillage operation on seedling emergence, crop growth and development, yield, residue decomposition, disease incidence and severity, quantification of pathogen propagules in soil and crop residue, and effects on the near-surface soil physical properties. The study was conducted during the 2010 and 2011 growing seasons at nine locations total for the two years throughout Kansas. The study compared vertical tillage against the producer’s current practice of no-till (NT), strip tillage (ST), or conventional disk (CD). Few significant differences were observed when studying soil properties, however not one treatment continuously had significant results and no trend was observed. Residue cover at all sites and across both years was significantly greater in the NT treatments. The residue cover also impacted the disease incidence and severity of Cercospora zea-maydis also known as gray leaf spot (GLS). Other diseases such as Marcophomina phaseolina and Fusarium spp. were not significantly impacted by one treatment or another. Overall, any differences in the soil, plant, and pathogen indicators have not resulted in significant yield improvements at any of the nine site locations of the two years of this study, but more site years will be needed to assess any potential benefits of VT. Information gained from this project will be disseminated to extension clientele including extension educators, producers, commodity groups, and agricultural professionals.
Keywords: tillage; soil properties; disease and pathogens; Agronomy (0285)